Embedded 3D Printing in Self‐Healing Annealable Composites for Precise Patterning of Functionally Mature Human Neural Constructs (Adv. Sci. 25/2022). Issue 25 (5th September 2022) - Kajtez, Janko; Wesseler, Milan Finn; Birtele, Marcella; Khorasgani, Farinaz Riyahi; Rylander Ottosson, Daniella; Heiskanen, Arto; Kamperman, Tom; Leijten, Jeroen; Martínez‐Serrano, Alberto; Larsen, Niels B.; Angelini, Thomas E.; Parmar, Malin; et al.
Abstract : Embedded 3D Printing In article number 2201392, Janko Kajtez, Jenny Emnéus, and co‐workers present a modular platform for bioengineering of neuronal networks via direct embedded 3D printing of human stem cells inside self‐healing annealable particle‐extracellular matrix (SHAPE) composites. The approach allows direct freeform patterning and functional maturation of human neural constructs. The image depicts deposition of cells inside SHAPE support to build human brain tissue.